1998
DOI: 10.1097/00007632-199802010-00022
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Spinal Angiomyolipoma With Extracanal Extension to the Thoracic Cavity

Abstract: Results of a literature survey of these tumors support management by prompt and radical surgical intervention for long-term cure, even in cases in which the infiltrating nature is recognized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…Rarely, spinal epidural angiolipomas show infiltrative behavior. 7,8,10,16,[19][20][21][22][23][24] Trabulo et al 5 highlight that it is not clear if the infiltrative angiolipomas originate in the epidural space and infiltrate the bone, or if they originate in the bone and spread to the epidural space or if they arise in both compartments simultaneously. Infiltration of the vertebral body is often associated with anterior localization.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Rarely, spinal epidural angiolipomas show infiltrative behavior. 7,8,10,16,[19][20][21][22][23][24] Trabulo et al 5 highlight that it is not clear if the infiltrative angiolipomas originate in the epidural space and infiltrate the bone, or if they originate in the bone and spread to the epidural space or if they arise in both compartments simultaneously. Infiltration of the vertebral body is often associated with anterior localization.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the international literature since 1892 to 2002 revealed 83 cases of spinal extradural angiolipomas including our two cases. [4][5][6][7][8][9] Most spinal angiolipomas are found at thoracic level and arise in the posterior extradural space. [4][5][6][7][8][9] Pure lumbar localization is extremely rare.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations